(untitled) (Voice: A Biannual & Bilingual Journal, 2025)
Economic growth in Nepal is also a priority of financial inclusion due to the Digital Nepal Framework and FinTech and digital payments strategies of Nepal Rastra Bank, which have seen the number of bank accounts rise substantially, to 81 percent by 2022. The major programs are the formation of a retail payment switch, the advancement of mobile banking, and the development of a strong legal framework on the financial services, and consumer protection and financial literacy as a tool to enhance inclusive economic growth. Financial inclusion is actually important as it can contribute to the reduction of poverty and lessening the poor-rich divide, that is why the government officials and regulators are giving it so much focus.